Weather Information for Garden City, 2015 - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2016)
Precipitation for 2015 totaled 23.27 in. This was 4.03 in. above the 30-year average of 19.24 in. and was nearly identical to 2014. Significant blowing dust was not observed in 2015. May and July had notably high precipitation with 6.38 in. and 5.36 in., respectively, which nearly doubled normal precipitation for these months. Hail was not observed in 2015. The largest daily rainfall was 1.94 in. on October 22. Sixteen days in May recorded measurable moisture.
Keywords: Garden City weather; 2015 weather